Determination of rivaroxaban in patient’s plasma samples by anti-Xa chromogenic test associated to High Performance Liquid Chromatography tandem Mass Spectrometry (HPLC-MS/MS) - Derogis, Priscilla Bento Matos; Sanches, Livia Rentas; de Aranda, Valdir Fernandes; Colombini, Marjorie Paris; Mangueira, Cristóvão Luis Pitangueira; Katz, Marcelo; Faulhaber, Adriana Caschera Leme; Mendes, Claudio Ernesto Albers; Ferreira, Carlos Eduardo dos Santos; França, Carolina Nunes; Guerra, João Carlos de Campos (PloS one, 2017)
Rivaroxaban is an oral direct factor Xa inhibitor, therapeutically indicated in the treatment of thromboembolic diseases. As other new oral anticoagulants, routine monitoring of rivaroxaban is not necessary, but important in some clinical circumstances. In our study a high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method was validated to measure rivaroxaban plasmatic concentration. Our method used a simple sample preparation, protein precipitation, and a fast chromatographic run. It was developed a precise and accurate method, with a linear range from 2 to 500 ng/mL, and a lower limit of quantification of 4 pg on column. The new method was compared to a reference method (anti-factor Xa activity) and both presented a good correlation (r = 0.98, p < 0.001). In addition, we validated hemolytic, icteric or lipemic plasma samples for rivaroxaban measurement by HPLC-MS/MS without interferences. The chromogenic and HPLC-MS/MS methods were highly correlated and should be used as clinical tools for drug monitoring. The method was applied successfully in a group of 49 real-life patients, which allowed an accurate determination of rivaroxaban in peak and trough levels.